Early prediction of hypertension during pregnancy in a low‐resource setting. Issue 2 (7th November 2015) - Kumar, Manisha; Gupta, Usha; Bhattacharjee, Jayashree; Singh, Ritu; Singh, Shalini; Goel, Manish; Sharma, Karuna; Rehman, Mujeeb U.
Abstract: Objective: To evaluate the role of maternal factors, biomarkers, and uterine‐artery Doppler in the prediction of hypertension during pregnancy. Methods: A prospective cohort study was performed between December 2012 and November 2014. All singleton pregnancies between 11 weeks and 13 weeks, 6 days of pregnancy were included. Patients had their body mass index (BMI, calculated as weight in kilograms divided by the square of height in meters), mean arterial pressure, uterine‐artery Doppler pulsatility index, and pregnancy‐associated plasma protein A (PAPP‐A) and free β‐human chorionic gonadotropin levels recorded. Any patients diagnosed with hypertension during follow‐up were assigned to the case cohort; all other patients were assigned to the control group. Results: Hypertension during pregnancy was observed in 198 (9.7%) of 2042 patients that attended follow‐up. The mean BMI, mean arterial pressure, uterine‐artery Doppler pulsatility index, and the PAPP‐A level at study enrollment were all significantly correlated with the later development of hypertension ( P < 0.001 for all variables). The combined sensitivity, specificity, positive predictive value, and negative predictive value of using the investigated parameters to predict hypertension was 76%, 80%, 31%, and 93%, respectively. Conclusion: Patient BMI, mean arterial pressure, PAPP‐A, and pulsatility index were found to be effective predictors of hypertension during pregnancy. Combining these predictors may be beneficial in selecting individuals for close monitoring and early intervention during pregnancy.